Evaluate learner satisfaction with the quality of training services of the University of Finance - Marketing - Truc, Ho Thanh; Oanh, Nguyen Thi Ngoc; Phung, Nguyen Thi Kim; Huong, Vo Thi Lan; Tien , Ngo Thanh (Tạp chí Nghiên cứu Tài chính - Marketing, 2024)
The objective of this research is to investigate how learner satisfaction is affected by aspects of service quality. Quantitative and qualitative research methods are used in this study. Accordingly, with a qualitative method, the study conducted in-depth interviews with 20 experts in the field of higher education to evaluate the completeness and validity of the scale. Using the quantitative method, the study conducted a survey with 1,405 learners at the University of Finance and Marketing (UFM) for the purpose of evaluating the reliability of the scale and, at the same time, being used to test the research model and proposed research hypotheses. The findings of the study indicate that learner satisfaction is influenced by eight independent components. Specifically, the most important component is image, which is followed by reliability, training programs, facilities, assurance, empathy, responsiveness, and lecturers. The research findings lead the authors to suggest that the UFM should concentrate on enhancing the university's reputation so that students feel proud of them; they should also follow through on their initial promises to students; evaluate and enhance their curricula to bring them closer to international standards, make them appropriate for students, and satisfy societal demands; To better serve students, upgrade the facilities.